Menuju Destinasi Pariwisata Berkelanjutan: Mengatasi Solusi Pengelolaan Sampah di Bali - Shantika, Budi; Wijaya, I Nyoman Cahyadi (Badan Riset dan Inovasi Daerah Provinsi Bali, 2024)
Purpose: This research aims to examine the challenges in waste management in Bali, with a focus on the role of the community in supporting sustainable tourism practices. Research methods: This research combines qualitative interviews with community leaders and analysis of quantitative data on waste management from various initiatives. Results and discussion: Community involvement significantly increases the effectiveness of waste management strategies. In particular, initiatives such as waste banks and local clean-up campaigns have galvanized community participation, resulting in increased recycling rates and reduced waste in affected areas. Empowering local communities results in innovative solutions and a stronger sense of ownership of environmental issues for sustainable tourism practices. Implication: Policymakers should prioritize community-based approaches in waste management strategies to achieve successful sustainable tourism practices. Keywords: Bali waste management, community engagement, sustainable tourism, environmental sustainability